Carbon sequestration pathways in microorganisms: Advances, strategies, and applications - Shupeng Ruan; Yuchen Jiang; Aoxue Wang; Xinying Zhang; Ying Lin; Shuli Liang (Engineering Microbiology)
In recent years, industrial activities have significantly increased atmospheric CO2 levels, exacerbating global warming. Carbon reduction involves implementing measures to minimize CO2 emissions from human activities and achieve a balance between carbon absorption and emissions. Therefore, effective reduction of CO2 emissions is crucial. Conventional physical and chemical methods for CO₂ fixation frequently cause secondary environmental pollution. As a result, utilizing microorganisms for CO2 fixation has gained considerable interest. This review provides an overview of the natural pathways for microbial CO2 fixation, recent advancements in artificial CO2 fixation, and strategies for enhancing the efficiency of microbial CO2 fixation. We also discuss the conversion of CO2 into diverse metabolic products and high-value chemicals. By identifying efficient carbon fixation pathways for microorganisms, this review aims to lay the foundation for the biological production of high-value chemicals using CO2 as a raw material.